Cooperative and non-cooperative sensitization upconversion in lanthanide-doped LiYbF4 nanoparticles. Issue 19 (3rd May 2017) - Zou, Qilin; Huang, Ping; Zheng, Wei; You, Wenwu; Li, Renfu; Tu, Datao; Xu, Jin; Chen, Xueyuan
Abstract : We demonstrate for the first time the phonon-assisted cooperative sensitization upconversion with a quantum yield of 0.0085% in LiYbF4 :Tb 3+ upconversion nanoparticles. Abstract : Lanthanide (Ln 3+ )-doped upconversion nanoparticles (UCNPs) have attracted tremendous interest owing to their potential bioapplications. However, the intrinsic photophysics responsible for upconversion (UC) especially the cooperative sensitization UC (CSU) in colloidal Ln 3+ -doped UCNPs has remained untouched so far. Herein, we report a unique strategy for the synthesis of high-quality LiYbF4 :Ln 3+ core-only and core/shell UCNPs with tunable particle sizes and shell thicknesses. Energy transfer UC from Er 3+, Ho 3+ and Tm 3+ and CSU from Tb 3+ were comprehensively surveyed under 980 nm excitation. Through surface passivation, we achieved efficient non-cooperative sensitization UC with absolute UC quantum yields (QYs) of 3.36%, 0.69% and 0.81% for Er 3+, Ho 3+ and Tm 3+, respectively. Particularly, we for the first time quantitatively determined the CSU efficiency for Tb 3+ with an absolute QY of 0.0085% under excitation at a power density of 70 W cm −2 . By means of temperature-dependent steady-state and transient UC spectroscopy, we unraveled the dominant mechanisms of phonon-assisted cooperative energy transfer ( T > 100 K) and sequential dimer ground-state absorption/excited-state absorption ( T < 100 K) for the CSU process in LiYbF4 :Tb 3+ UCNPs.